2013
DOI: 10.1007/s11764-012-0258-2
|View full text |Cite
|
Sign up to set email alerts
|

Employment outcomes among survivors of common cancers: the Symptom Outcomes and Practice Patterns (SOAPP) study

Abstract: Introduction Risk factors for employment difficulties after cancer diagnosis are incompletely understood, and interventions to improve post-cancer employment remain few. New targets for intervention are needed. Methods We assessed a cohort of 530 nonmetastatic cancer patients (aged≤65 years, >6 months from diagnosis, off chemo- or radiotherapy) from the observational multi-site Symptom Outcomes and Practice Patterns study. Participants reported employment change, current employment, and symptoms. Groups were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
59
0
5

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(65 citation statements)
references
References 63 publications
1
59
0
5
Order By: Relevance
“…Previous studies have indeed found such an association between better psychosocial outcomes and less healthcare utilization or costs[13141516] and higher rates of return to work. [1718] However, other studies did not found such an association. [1920]…”
Section: Introductionmentioning
confidence: 98%
“…Previous studies have indeed found such an association between better psychosocial outcomes and less healthcare utilization or costs[13141516] and higher rates of return to work. [1718] However, other studies did not found such an association. [1920]…”
Section: Introductionmentioning
confidence: 98%
“…Cancer-related fatigue is one of the most common long-term debilitating toxicities experienced by approximately 30% of women previously treated for breast cancer (Bower et al, 2009; Geinitz et al, 2001; Giese-Davis et al, 2011; Kesler et al, 2012; Shapiro and Recht, 2001; Tevaarwerk et al, 2013; Wratten et al, 2004). Increasing data suggest that cancer-related fatigue is associated with a heightened inflammatory response (Bower et al, 2011; Wang et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Employment provides a number of important benefits to individuals, including economic stability, professional identity, supportive social relationships [1] and maintaining a sense of normalcy and control [2]. A cancer diagnosis can cause a major disruption to an individual's employment, which can subsequently affect the abovementioned quality of liferelated factors.…”
mentioning
confidence: 99%